2017
DOI: 10.1186/s12891-017-1545-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional daily diary of fatigue-fibromyalgia-17 items (MDF-fibro-17): part 2 psychometric evaluation in fibromyalgia patients

Abstract: BackgroundThe Multidimensional Daily Diary of Fatigue-Fibromyalgia-17 instrument (MDF-Fibro-17) has been developed for use in fibromyalgia (FM) clinical studies and includes 5 domains: Global Fatigue Experience, Cognitive Fatigue, Physical Fatigue, Motivation, and Impact on Function. Psychometric properties of the MDF-Fibro-17 needed to demonstrate the appropriateness of using this instrument in clinical studies are presented.MethodsPsychometric analyses were conducted to evaluate the factor structure, reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Regarding internal consistency, the results of the present research showed that composite reliability coefficients showed acceptable internal consistency [35]. Similar results have been reported elsewhere [12], showing a good degree of reliability of the current translated versions.…”
Section: Factorial Validity Of the Mdf-fibro-17supporting
confidence: 91%
See 4 more Smart Citations
“…Regarding internal consistency, the results of the present research showed that composite reliability coefficients showed acceptable internal consistency [35]. Similar results have been reported elsewhere [12], showing a good degree of reliability of the current translated versions.…”
Section: Factorial Validity Of the Mdf-fibro-17supporting
confidence: 91%
“…Since no cross-loadings were detected and dimension removal did not increase the model fit, the dimensions were retained, and the researchers went on to examine other statistical tests for scale validity. Li and colleagues [12] only found discriminant validity issues between the motivation and physical fatigue dimensions. This can be related to the overall perception of fatigue in patients with FM with different cultural backgrounds.…”
Section: Factorial Validity Of the Mdf-fibro-17mentioning
confidence: 99%
See 3 more Smart Citations